UNVEILING THE NATURE OF UNIDENTIFIED GAMMA-RAY SOURCES. II. RADIO, INFRARED, AND OPTICAL COUNTERPARTS OF THE GAMMA-RAY BLAZAR CANDIDATES - Massaro, Francesco; D'Abrusco, Raffaele; Paggi, Alessandro; Masetti, Nicola; Giroletti, Marcello; Tosti, G.; Smith, Howard A.; Funk, Stefan (Astrophysical Journal Supplement Series, 2013)
A significant fraction (similar to 30%) of the high-energy gamma-ray sources listed in the second Fermi Large Area Telescope catalog (2FGL) are still of unknown origin, being not yet associated with counterparts at low energies. We recently developed a new association method to identify if there is a. gamma-ray blazar candidate within the positional uncertainty region of a generic 2FGL source. This method is entirely based on the discovery that blazars have distinct infrared colors with respect to other extragalactic sources found, thanks to the Wide-field Infrared Survey Explorer (WISE) all-sky observations. Several improvements have also been performed to increase the efficiency of our method in recognizing. gamma-ray blazar candidates. In this paper we applied our method to two different samples, the first constituted by unidentified. gamma-ray sources (UGSs), and the second by active galaxies of uncertain type, both listed in the 2FGL. We present a catalog of IR counterparts for similar to 20% of the UGSs investigated. Then, we also compare our results for the associated sources with those present in the literature. In addition, we illustrate the extensive archival research carried out to identify the radio, infrared, optical, and X-ray counterparts of the WISEselected,. gamma-ray blazar candidates. Finally, we discuss the future developments of our method based on ground-based follow-up observations.
CRIS-Team WoS Importer:2020-01-15